State, Religion, and Revolution in Iran, 1796 to the Present - Moazami, Behrooz; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book examines transformation of political and religious spheres in Iran from the start of the Qajar period to the dramatic post-election crisis of 2009. It challenges dominant scholarly assumptions about the influence of Shi'ism in Iranian culture and the role of religious elites.
Keywords: Science; Science; Science, general